Immunosuppression for Connective Tissue Disease–Related Pulmonary Disease - Maher, Toby M. (Seminars in Respiratory and Critical Care Medicine, 2014)
With improvements in the systemic treatment of the various connective tissue diseases (CTDs) the pulmonary complications of these conditions are now, for many patients, the major cause of morbidity and impaired quality of life. Furthermore, at least in scleroderma, pulmonary disease has become the leading cause of death for this patient group. Although, the pathogenesis of CTD-related pulmonary disease is poorly understood there is an assumption that it arises as a sequelae of immune-mediated injury to the lung. As a result, immunosuppressant agents form the mainstay of treatment for pulmonary disease occurring in the context of CTD. There is, however, a paucity of clinical trial data available to inform treatment decisions across the spectrum of CTD-related pulmonary disease. The best available evidence has been generated in scleroderma-associated interstitial lung disease. Therefore, treatment decisions are informed by registry data, case series, and individual case reports. With this in mind, corticosteroids together with azathioprine and mycophenolate mofetil are widely used for the management of mild disease or as a maintenance therapy, while cyclophosphamide and rituximab have emerged as treatments for refractory or rapidly progressive disease. This article examines the data underpinning the use of different immunosuppressants in CTD-associated pulmonary disease while highlighting limitations in the existing knowledge base and identifying questions for future clinical study.
Keywords: interstitial lung disease; rituximab; cyclophosphamide; systemic sclerosis; therapy; polymyositis; pulmonary vasculitis